A Study of Pedagogical Inputs of Learning Outcomes with Respect to Teachings of Bhagavad Gita - Chand, Dr. Bharati (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
This paper presents pedagogical inputs of learning outcomes based on Blooms Taxonomy in respect to teachings of Bhagavad-Gita. The Blooms Taxonomy of Educational Objectives classified into three domains namely cognitive domain, affective domain and psychomotor domain which are just equivalent to three disciplines of Bhagavad-Gita namely knowledge, devotion and action respectively. This paper saught to investigate systematically chapter-wise pedagogical inputs of Bhagavad Gita and learning outcome which are presented cohesively based on cognitive, affective and psychomotor of Blooms Taxonomy of educational objectives. This paper is based on literature review and hermeneutics, a qualitative research methodology which involves study, understanding and interpretation of ancient or classical text. The existing findings are interpreted by analyzing the contents of Bhagavad Gita. Three paths of knowledge, devotion and action enshrined in Bhagavad-Gita, are not independent of one another, but they together form a synthetic whole. This study aims to gain deep understanding and insights into three domains of Blooms Taxonomy like cognitive, psycho motor and affective domains and three paths of Jnana Yoga, Karma Yoga and Bhakti yoga are complementary as well as supplementary to each other